Benin : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
Benin's program furthers the objectives elaborated in the previous report. It is the result of a broad participative process that engaged all levels of government, the private sector, civil society, and donor partners. Executive Directors commend the program as it provides an adequate framework for poverty reduction. The strategy addresses the critical constraints and challenges facing Benin and builds on its comparative advantages. However, it lacks the specificity required to ensure results. Improving alignment of necessary actions and activities in support of the objectives with realistically available resources will help.